2008
DOI: 10.1007/s11165-008-9087-8
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of Biodiversity as a Challenge for Sustainable Development: How Do Pupils in Chile and Germany Perceive Resource Dilemmas?

Abstract: The topic of biodiversity is of high value for education for sustainable development as it reflects the interaction of ecological, economic and social issues particularly well. Especially in so-called biodiversity hotspots, among them Chile, natural resources are often depleted for economic interest which, in many cases, is required income. Therefore, economic and social aspects must be considered in order to fully understand biodiversity loss. Being such an important issue, it is surprising that little is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 22 publications
3
43
0
7
Order By: Relevance
“…For example, Menzel and Bögeholz [22] found that German and Chilean high school students had problems identifying the social and economical dimensions of the extraction of wild Boldo (Peumus boldus) leaves in Chile and bulbs of Devil's claw (Harpagophytum procumbens) in Namibia. With respect to Turkish students, the same result was observed concerning the exploitation of wild Salep (Orchis mascula) in Anatolia [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Menzel and Bögeholz [22] found that German and Chilean high school students had problems identifying the social and economical dimensions of the extraction of wild Boldo (Peumus boldus) leaves in Chile and bulbs of Devil's claw (Harpagophytum procumbens) in Namibia. With respect to Turkish students, the same result was observed concerning the exploitation of wild Salep (Orchis mascula) in Anatolia [23].…”
Section: Discussionmentioning
confidence: 99%
“…The low performance is likely related to an overly strong focus on ecological knowledge in teaching natural resource use issues and/or sustainable development [22,42]. Even the broad interdisciplinary concept of sustainable development is taught mostly in the natural sciences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La pérdida de la biodiversidad se constituye en el eje de investigación de varios autores, quienes se interesan por indagar: a) Los conocimientos acerca de las causas y las consecuencias; b) Las actitudes y formas de valorar; c) Su relación en las escalas local-global, y d) Medios de comunicación y fuentes de información (Ballouard, 2007;Ballouard, et al, 2011;Dalelo, 2012;Dikmenli, 2010;Fiebelkorn, et al, 2012;Hunter, et al, 2003;Hyseni, 2008;Jimmy, 2006;Lindemann, et al, 2009;Menzel, et al, 2009;Sadik, et al, 2007;Tanner, 2010;The Gallup Organization Hungary, 2007).…”
Section: ) Pérdida De La Biodiversidadunclassified
“…Los propósitos varían, al hacer énfasis en: a) La biodiversidad como un tema de la EA y de la EDS; b) Como estrategia del programa de la EA y la EDS; c) Formación ciudadana y d) Alfabetización ecológica. (Collins, 2012;Fernández, 2000;Helldén, et al, 2008;Kanno, et al, 2011;Kobori, 2009;Lindemann, 2002;McLaughlin, et al, 2006;Menzel, et al, 2009;Menzel, et al, 2010;Ramadoss, et al, 2011;Ulbrich, et al, 2010;Van Weelie, et al, 2002).…”
Section: ) Educación Ambiental (Ea)-educación Para El Desarrollo Sosunclassified